Women's Self-Report of Sexual Victimization: An Experimental Examination of the Influence of Race, Mode of Inquiry, Setting, and Researcher Contact. (June 2017) - McCallum, Ethan B.; Peterson, Zoë D.
Female college students ( N = 255) provided self-report of adult sexual assault (ASA) and child sexual abuse (CSA) in one of eight randomly assigned conditions which manipulated three methodological variables (level of researcher contact, setting, and inquiry mode). The impact of methodology on reporting was examined, with race as a moderator. Non-White participants reported significantly more CSA than White participants out of lab, but differences were not observed in lab. White participants reported significantly more ASA than non-White participants on pencil-and-paper surveys, but there were no differences on computer surveys. Interpretation of race-related differences in self-reported victimization may require consideration of methodological effects.